Об интегрирующем множителе уравнений динамики твердого тела на инвариантных многообразиях - Горр, Г.В.; Щетинина, Е.К. (Видавничий дім "Академперіодика" НАН України, 2007)
The sufficient conditions for the existence of the integrating factor of a system of n differential equations of the rigid body dynamics, which allow n – 3 first integrals and one invariant relation or n – 4 first integrals and two invariant relations are obtained. The connection with the theory of Jacobi' integrating factor is shown.